Kegiatan Bermain Floortime untuk Meningkatkan Interaksi Sosial pada Anak dengan Autism Spectrum Disorder (ASD) - Yulita Anggelia; Endeh Azizah; Ira Adelina (Humanitas (Jurnal Psikologi), 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments, particularly in the domains of communication and social interaction. One approach that has been found to be effective in improving social interaction skills in children with ASD is the Developmental, Individual-differences, Relationship-based (DIR) Floortime approach. In this study, the DIR Floortime intervention was structured into six sessions, based on the first three developmental stages of emotional functioning proposed by Greenspan (2006), namely self-regulation and interest in the world, forming relationships and attachment, and intentional two-way communication. The participants in this study were five children diagnosed with ASD. The results indicated a significant improvement in social interaction following the intervention (p = 0.042). This finding was further supported by increased scores on the Functional Emotional Assessment Scale (FEAS) observed across sessions for each participant. In conclusion, Floortime play-based intervention can effectively enhance social interaction skills in children with ASD.